Keadilan dalam Keluarga: Poligami - Zuraidah Zuraidah (An Nisa'a, 2012)
Polygamyis oneproblem inmarriagesamongthe mostcontroversialdebatesat once. Polygamyis rejectedwith a variety ofargumentsnormative, psychological, andevenalways associated withinjusticegander. Islamhas giventhe conditionson thedemandofa Muslimwhopractice polygamyisjusticeto himself that hewoulddo justicetohis wivesin terms offood, clothing, andliving(physical and spiritual). But ifhe islesssure of himselfto be able todo justice tohis wives, he was notallowedtopractice polygamy.